What Financial Literacy and Saving Behavior Reveal About Retirement Planning: A Case Study of CV. Mulia Pratama - Afifah Usman, Nurul; Mardhatillah, Dinda (Salam (Islamic Economics Journal), 2025)
According to OJK data, only 15% of those employed has planned retirement programs, with a lower percentage in the private sector. This highlights the substantial obstacles that private sector employees in Indonesia confront when preparing for retirement. Santoso et al. (2022) conducted research that indicates that 90% of private employees are not provided with retirement program facilities by their employers, resulting in a significant welfare disparity in comparison to civil servants. This issue is further exacerbated by a number of factors, including low financial literacy (49.68% nationally in 2022), unbalanced consumption patterns, poor saving behavior that prioritize short-term needs, global economic uncertainties, high inflation rates, and the demographic challenge of Indonesia's aging population. This study looks into how saving behavior and financial literacy affect retirement planning among the employees at CV. Mulia Pratama. The aim is to provide stakeholders information they can use in designing improved retirement planning programs for Indonesian private sector employees.   Keywords: financial literacy, saving behavior, retirement planning